Development of Multi-Tier Diagnostic Tests for Primary Schools: A Systematic Literature Review - Auliya, Hafizhah Rahmiati; Christianti, Martha; Hidayat, Benny (Jurnal Prima Edukasia, 2025)
The implementation of multi-tiered diagnostic tests is crucial for identifying and addressing student misconceptions in primary education. This study systematically reviews the development and application of these diagnostic tools in primary schools from 2019 to 2024. Following the PRISMA protocol, 26 studies were selected from an initial 178 records obtained from the Scopus database. The analysis highlights trends in test development, key content areas, and potential future applications in primary mathematics education. The findings emphasize the importance of tailored diagnostic tools for early identification of misconceptions and suggest directions for future research to enhance their effectiveness in educational assessments.